Komunikasi Peningkatan Akreditasi Program Studi - Azman Sulaiman; Hanifah Nurdin; Teuku Zulyadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Accreditation of the Study Program is a must to ensure that there is no expiration. Because it will have an effect on the consequences for the existence of the study program which is determined by the National Accreditation Board for Higher Education (BAN PT). Preparing for accreditation is not an easy thing to get a decent accreditation value, but it requires support and cooperation with all parties. However, the problems that occur are many parties who do not seriously support the accreditation process, especially the lecturers, students and alumni. Therefore, proper communication is needed so that the cohesiveness and seriousness of all parties emerge. This article discusses how communication is built to increase cooperation, cohesiveness and seriousness in preparing for accreditation so as to increase the value of accreditation. The method used is qualitative descriptive analysis. Research workshop in the Study Program. KPI Postgraduate IAIN Lhokseumawe by using organizational information theory. The results of the study show that the IAIN Lhokseumawe Postgraduate KPI Study Program communicates with the Rector, Lecturers, LPM, Students, Alumni, Alumni Users and Assessors in the process of increasing their accreditation. Communication built in the form of formal, informal and persuasive communication. Especially the head of the study program always communicates with increasing emotional relationships for the benefit of the study program